Efectos del biol bovino en rendimientos de biomasa verde y valores nutricionales del pasto saboya (Megathyrsus maximus) - Villamar Moreira, Jean Pierre (2022)
The present research work aimed to evaluate the effect of Biol (Bovine) on green biomass yields and nutritional values of Savoy grass (Megathyrsus maximus) for which a Completely Random Block Design was carried out in which three levels of fertilizers were applied in different concentrations distributed in plots of 2x2 m with five repetitions each treatment. The treatments in this research were T0: 0 %, T1: 10 %, T2: 20 % and T3: 30 % of Biol, morphological variables of plant height, leaf width and green fodder production per hectare were considered, while in the nutritional variables the percentages of protein, dry matter, crude fiber and ash were evaluated. The results obtained did not present significant differences (P>0.05). The cost of producing Biol was 30.51 dollars, an affordable price for the producer's economy, unlike chemical fertilizers that are of high economic costs. It is concluded that the levels of bovine Biol had no effect on the production of green biomass and nutritional assessment of Savoy grass (Megathyrsus maximus).